Micro Waqf Banks (BWM) Development in Indonesia - Zainudin, Zulkifli; Aziz, Helmi Mundhiya; Suhendra (The Economic Review of Pesantren, 2024)
Bank Waqf Micro (BWM) is an Islamic microfinance instrument developed to increase financial inclusion, empower micro businesses, and free the community from loan shark practices. Nevertheless, the implementation and development of BWM in Indonesia still faces various structural, institutional, and operational constraints. This study aims to identify and determine the priorities of the main problems in the development of Micro Waqf Banks in Indonesia based on the perspective of experts. The method used is the Delphi method involving nine experts from academics, practitioners, and regulators in the field of microfinance and Islamic economics. Data analysis was carried out using statistical indicators of mean value, standard deviation, and interquartile range (IR) to assess the consensus level. The results showed that of the 25 problem variables identified, there were 16 variables that reached a consensus. The three main priorities for BWM development in Indonesia are coaching and education for BWM managers, the role of BWM in freeing the community from loan sharks, and the need for reliable infrastructure and information technology support. These findings are expected to be the basis for the formulation of policies and strategies to strengthen BWM institutions in Indonesia